(untitled) (Research, Society and Development, 2024)
The management of post-surgical patients in ICUs is challenging due to the severity of the conditions and the need for advanced interventions. Immunomodulatory therapies have been studied as a promising strategy to improve clinical outcomes by regulating the immune response and reducing complications after surgery. Objective and Methodology: The objective of this article is to present an integrative bibliographic research study of immunomodulatory therapies in post-surgical patients in Intensive Care. Results and Discussions: The variety of applications of immunomodulators, including treatments for critical conditions such as Stevens-Johnson Syndrome, sepsis and Systemic Inflammatory Response Syndrome (SIRS). Significant advances have been observed in biologics, immunotherapy, cellular therapies, and immunonutrients, with documented safety and efficacy profiles. Treated patients had a lower incidence of nosocomial infections and a reduction in inflammatory markers, such as CRP and IL-6, contributing to clinical improvements in the ICU. Conclusion: Highlights the benefits of immunomodulatory therapies in reducing complications and controlling inflammatory responses, although it warns about associated risks, such as inadequate immune suppression. More research is needed to integrate these therapies into standard clinical protocols, ensuring maximum effectiveness and full understanding of the benefits and risks involved.